The Neuronal Correlates of Indeterminate Sentence Comprehension: An fMRI Study - de Almeida, Roberto G.; Riven, Levi; Manouilidou, Christina; Lungu, Ovidiu; Dwivedi, Veena D.; Jarema, Gonia; Gillon, Brendan (Frontiers in Human Neuroscience, 2016)
Sentences such as "The author started the book" are indeterminate because they do not make explicit what the subject (the author) started doing with the object (the book). In principle, indeterminate sentences allow for an infinite number of interpretations. One theory, however, assumes that these sentences are resolved by semantic coercion, a linguistic process that forces the noun "book" to be interpreted as an activity (e.g., writing the book) or by a process that interpolates this activity information in the resulting enriched semantic composition. An alternative theory, pragmatic, assumes classical semantic composition, whereby meaning arises from the denotation of words and how they are combined syntactically, with enrichment obtained via pragmatic inferences beyond linguistic-semantic processes. Cognitive neuroscience studies investigating the neuroanatomical and functional correlates of indeterminate sentences have shown activations either at the ventromedial pre-frontal cortex or at the left inferior frontal gyrus. These studies have supported the semantic coercion theory assuming that one of these regions is where enriched semantic composition takes place. Employing fMRI, we found that indeterminate sentences activate bilaterally the superior temporal gyrus, the right inferior frontal gyrus, and the anterior cingulate cortex, more so than control sentences ("The author wrote the book"). Activation of indeterminate sentences exceeded that of anomalous sentences ("…drank the book") and engaged more left- and right-hemisphere areas than other sentence types. We suggest that the widespread activations for indeterminate sentences represent the deployment of pragmatic-inferential processes, which seek to enrich sentence content without necessarily resorting to semantic coercion.